The growth hormone secretagogue hexarelin stimulates the hypothalamo-pituitary-adrenal axis via arginine vasopressin. - Korbonits, M; Kaltsas, G; Perry, L; Putignano, P; Grossman, AB; Besser, G; Trainer, P (1999)
GH secretagogues (GHSs) act via specific receptors in the hypothalamus and the pituitary gland to release GH. GHSs also stimulate the hypothalamo-pituitary-adrenal (HPA) axis via central mechanisms probably involving CRH or arginine vasopressin (AVP). We studied the effects of hexarelin, CRH, and desmopressin, an AVP analog, on the stimulation of the HPA axis in 15 healthy young male volunteers. Circulating ACTH, cortisol, GH and PRL concentrations were measured for 2 h after the injection of hexarelin, CRH, or desmopressin alone and the combination of hexarelin plus CRH or hexarelin plus desmopressin. Symptoms during the tests were assessed by visual analog scales. Hexarelin significantly increased ACTH and cortisol release (area under the curve, 3,444+/-696 ng/L x 125 min and 45,844+/-2,925 nmol/L x 125 min, respectively), and this effect was augmented by the addition of CRH in a dose that on its own produces maximal stimulation (6,580+/-1,572 ng/mL x 125 min and 63,170+/-2,616 nmol/L x 125 min; P = 0.01 and 0.001, respectively), but was not influenced by the addition of desmopressin (3,540+/-852 ng/mL x 125 min and 35,319+/-3,252 nmol/L x 125 min; not significant). CRH on its own caused similar or slightly higher ACTH and cortisol release than hexarelin alone. Desmopressin given alone elicited a rapid rise in circulating ACTH and cortisol, but its effects were less than those of any other treatment and were not augmented by hexarelin. Hexarelin also caused significant GH and PRL release, but these effects were not influenced by the coadministration of CRH or desmopressin. Visual analog scales showed an acute small increment in appetite with hexarelin. Our data suggest that the effect of GHSs on the HPA axis involve at least in part the stimulation of AVP release. In summary, we have shown that in healthy male volunteers, the effect of hexarelin on the HPA axis does not involve CRH, but may occur through the stimulation of AVP release.